2018
DOI: 10.1590/s1517-707620180004.0584
|View full text |Cite
|
Sign up to set email alerts
|

Consistency analysis of mechanical properties of elements produced by FDM additive manufacturing technology

Abstract: Additive manufacturing (AM) technology refers to the process of producing 3D objects by adding material in successive layers. Fused deposition modeling (FDM) is one of the AM technologies where objects are built by adding layers of melted thermoplastic filament onto the printing surface. Mechanical properties of FDM printed part depend on many influencing factors such as material composition, extruding temperature, printing parameters and environment temperature. The aim of this study was to investigate consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 38 publications
2
37
0
4
Order By: Relevance
“…The specimens after tensile testing are presented in Figure 8. Most of them break in close to the radius of fillet close to the grips, which is common for FDM specimens [27], and it is due to stress concentrations at fillet areas [10], being the kind of fracture brittle, with no plastic deformation observed. As Wu et al reported [28], craze is the main plastic deformation mechanism of ABS, and a great number of crazes are generated perpendicular to the load direction.…”
Section: Mechanical Behavior Of Solid Specimensmentioning
confidence: 99%
See 2 more Smart Citations
“…The specimens after tensile testing are presented in Figure 8. Most of them break in close to the radius of fillet close to the grips, which is common for FDM specimens [27], and it is due to stress concentrations at fillet areas [10], being the kind of fracture brittle, with no plastic deformation observed. As Wu et al reported [28], craze is the main plastic deformation mechanism of ABS, and a great number of crazes are generated perpendicular to the load direction.…”
Section: Mechanical Behavior Of Solid Specimensmentioning
confidence: 99%
“…Comparison of mechanical properties in samples with solid (ASTM-O1, ASTM-O2) and non-solid (S1, S2, S3) infill. Tensile strengths of ABS parts obtained by FDM have been reported to be in the range of 11-40 MPa [10]; the explanation to this wide range is associated to their anisotropic behavior. Results are in good agreement with previous works such as the one by Tymrak et al [33], with tensile strengths around 30 MPa, or the work by Banjanin et al [10], with an average value of tensile stresses for ABS samples of 31 MPa, considering that they used non-solid specimens, so they are expected to have lower values than the ones obtained in our work with solid ones; in fact, these reference values are in very good agreement with the ones obtained in our previous work with non-solid samples [26], used for comparison in this section.…”
Section: Comparative Analysis With Conventional Samples With Pattern mentioning
confidence: 99%
See 1 more Smart Citation
“…Una de las principales problemáticas que presenta esta tecnología es la elección de los parámetros de impresión correctos de acuerdo con el material [6], ya que estos afectan las propiedades mecánicas y la capacidad de uso final de la pieza [7]. Se han realizado diferentes estudios en los que se analiza la dependencia de las propiedades mecánicas con los parámetros de impresión para piezas fabricadas con filamentos de acrilonitrilo butadieno estireno (ABS) y ácido poliláctico (PLA) [8][9][10][11], materiales poliméricos que son usados frecuentemente con este tipo de tecnología por ser los más estables [5].…”
Section: Introductionunclassified
“…The transition from "cut" to "printed" products raises the question of comparing their strength, especially for products, printed using FFF technology. It is related to the fact that due to the physical properties of polymeric materials, which are often used by this technology, when melting their macromolecules are stretched in the direction of flow, resulting in objects printed by the FFF method being characterized by anisotropy [5][6][7][8]. Test data comparison of samples printed from the most common acrylonitrile butadiene styrene (ABS) and polylactide (PLA) plastics with the results of samples being made, for example, with a screw extruder [9], does not speak in favor of 3D printing, if the load is applied not along, but across, the layers.…”
Section: Introductionmentioning
confidence: 99%